(untitled) (Fiep Bulletin - online, 2016)
Drug use among students has become a health concern public, because of increased use in social environment and the constant drug seizures in school settings. The first experiences with drugs often occur during adolescence, and therefore at this stage that young people are vulnerable psychological and social point of view. Studies claim that the severity of this problem shows that it is necessary to find new ways to address the issue, with the involvement of the whole society. The current National Education Policy and the National Policy on Drugs, Brazil, consider the school as the fundamental space to accommodate vulnerable young people through creative projects and actions that guarantee the right of the comprehensive development of students, providing teaching resources, welfare, cultural and health promotion, for the prevention of drug use, as well as its full removal of associated risk behavior.